TINJAUAN SPASIAL PRODUKSI PADI DALAM UPAYA MENINGKATKAN KETAHANAN PANGAN DI KABUPATEN BEKASI (Spatial Review of Rice Production Efforts in Improving Food Security in Bekasi District) - Rasminto Rasminto; Khausar Khausar; Cahyadi Setiawan (STKIP Bina Bangsa Meulaboh, 2018)
AbstractThis study is intended to identify spatial condition of rice production in 2010-2013 and it’s related factors to support foods security in Bekasi District. It uses secondary data from various agencies, while the analysis is spatial analysis with ArcGIS. The assumption is rice production spatial distribution can be an important review of foods security condition in Bekasi District. This spatial distribution can show the results of rice production in each zone Bekasi District. Rice is one of main commodity in agricultural sector that is also the main source of community’s needs fulfillment.Based on the distribution of monthly rainfall average in Bekasi, that the wet months occurred in January to April and October to December, while the dry months occurred in May to September. The areas that possess a high rice production is Pebayuran Suc-district, Sukawangi Sub-district and Tambelang Sub-district, low rice production is in Cikarang Utara Sub-district and Cikarang Barat Sub-district which is located in Bekasi Regency. In the management of agriculture, farmers in Bekasi not paying attention of resource management in particular aspects of a sustainable environment with high use of chemical fertilizers and pesticides.It can be seen from rice field’s management system which is carelessly and not notifying environment’s sustainability. It can be showed from a chemical fertilizers utilization that causing a degradation of wetland and rice production years by years.Keywords: spatial analysis, rice production, foods security